2013
DOI: 10.5964/pch.v2i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anxiety: Prevalence and Evaluation of Psychometric Properties of a Scale

Abstract: Aim: To estimate the reliability and validity of the Dental Anxiety Scale (DAS) and identify the prevalence and the effect of the socio-demographic characteristics of dental anxiety, in a sample of 212 adults. Methods: The psychometric sensitivity of the scale was assessed. A confirmatory factor analysis was performed, and the convergent validity and internal consistency were determined. The prevalence of anxiety was estimated, and the effect of socio-demographic variables on anxiety was assessed using structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 22 publications
9
21
1
1
Order By: Relevance
“…Results of this study showed a prevalence of 2.5% for extremely anxious individuals, considerably divergent from the results of 12.3% reported by Campos et al (2). …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Results of this study showed a prevalence of 2.5% for extremely anxious individuals, considerably divergent from the results of 12.3% reported by Campos et al (2). …”
Section: Discussioncontrasting
confidence: 99%
“…In this study, 52.5% of the sample consisted of low-anxiety individuals, a result similar to that of Campos et al (2) who reported a prevalence of 47.6%. Results of this study showed a prevalence of 2.5% for extremely anxious individuals, considerably divergent from the results of 12.3% reported by Campos et al (2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, anxiety can occur and has been measured in a variety of settings (e.g. at the dentist; Campos, Presoto, Martins, Domingos, & Maroco, 2013).…”
mentioning
confidence: 99%